Analisis Hukum Terhadap Perceraian Pada Kawin Sebongi Di Masyarakat Aceh Tenggara Menurut Undang-Undang No. 1 Tahun 1974 Tentang Perkawinan Dan Kompilasi Hukum Islam (Analisis Putusan Mahkamah Syariah Kutacane Nomor: 227/PDT.G/2017/MS KC) - Putri Ramadhona Rambe; Rosnidar Sembiring; Edy Ikhsan; Idha Aprilyana Sembiring (Iuris Studia: Jurnal Kajian Hukum, 2022)
The occurrence of divorce cases in sebongi marriages that occurred in the people of Southeast Aceh, namely the marriage age was so short that it was even only one night. So this study is intended to examine related to the problem of factors causing divorce in overnight marriages, legal protection for husbands due to divorce in a sebongi marriage according to Law No. 1 of 1974 concerning Marriage and KHI. As well as the basis for the judge's consideration in granting the divorce permit.The results of this study show that there are 4 (four) factors for the occurrence of divorce in a sebongi marriage in southeast Aceh society, namely the factor that the wife is no longer a virgin before marriage, the factor that the wife does not want to be invited to have sex, the factor that the wife has the intention to divorce before marriage and the factor of the bride's reluctance to return to the husband's house after the custom of winning. legal protection for the husband is the loss of the husband's obligation to provide a living to the wife due to the Nusyuz wife either living still in marriage or living iddah when there has been a divorce as explained in article 80 paragraph (7) and article 152 of the KHI